Extended liquid chromatography high resolution mass spectrometry screening method for veterinary drug, pesticide and human pharmaceutical residues in aquaculture fish. Issue 10 (3rd October 2019) - Turnipseed, Sherri B.; Storey, Joseph M.; Wu, I-Lin; Andersen, Wendy C.; Madson, Mark R.
ABSTRACT: A liquid chromatography high resolution mass spectrometry (LC-HRMS) screening method was developed previously to analyze for veterinary drug residues commonly found in different types of aquaculture products. This method has been further evaluated for its feasibility to detect several other classes of compounds that might also be a concern as possible contaminants in farmed tilapia, salmon, eel and shrimp. Some chemicals could contaminate water sources used in aquaculture production through agricultural run-off. These compounds include several widely used triazine herbicides, organophosphate and carbamate pesticides, as well as various discarded human pharmaceuticals. Other possible contaminants investigated were selected disinfectants, some newer antibiotics, growth promoters, and various parasiticides. The sample preparation consisted of an acidic acetonitrile extraction followed by solid-phase extraction clean-up. Data were collected with a quadrupole-Orbitrap MS using both non-targeted and targeted acquisition. This rapid clean-up procedure and HRMS detection method described previously for veterinary drug residues also worked well for many other types of compounds. Most analytes had screening limit levels between 0.5–10 ng/g in the matrices examined using exact mass identification criteria. The strategy described in this paper for testing the performance of additional analytes will help expand the applicability of the HRMS procedure as aquaculture samples can now be analyzed for a wider range of contaminants. Graphical Abstract: